ANALISIS KADAR NIKEL PADA PT.SINAR CIKOANG GEMILANG KECAMATAN BUNGKU TIMUR KABUPATEN MOROWALI - Ihzal Nurdin Tahir; Hendra Sani; Syamsuddin; Gina Audina (Journal Teknik Dan Teknologi, 2025)
Sinar Cikoang Gemilang Edifice is a company engaged in the mining sector, especially in nickel ore mine located in the village of buleleng Regency of morowali kecamatan bungku coastal province of Central Sulawesi. IUP Pt. SCG. PT. Sinar Cikoang Gemilang (SCG) is one of the laterite nickel mining company using the system of open mining (surface mining). Levels of supervision will be conducted strictly by Quality Control both from the front of the mine until the placement of ore in the area of the Stock Pile and continuously perform the taking of the sample to control grade and do blending ore with appropriate methods so that the desired levels can be achieved. The order of the mining activities in PT. Sinar Cikoang Gemilang includes disassembly, loading and hauling. PT. Sinar Cikoang Gemilang provides various mechanical tools in helping the forefront, such as gali transport tools, tools, fit and support. In conducting the activities of the mining of nickel ore (ore) is done by using the tool fit excavator and ore minerals results material loaded into dump trucks brought to the dom/stockpile. Research issues do occur between the mining front levels and stockpile as well as causative factor of difference. The purpose of the study to find out how large the difference levels and cause factor levels of distinction. To get the desired data will then be carried out observation/observation methods where the author will engage directly with activities on the spot. As for the results of the data mining in the production is a dom2:1.85, dom 3:1.76 and realization in the stockpile is dom 2:1.83, dom 3:1.79 and distortion levels to dom 2 amounted to 1.08% and 1.7% of dom 3. From the observations, then retrieved the factors cause decline tonage and decreased levels of among others the following: The skills of the operator when taking ore getting and mixing, Thoroughness in sampling, Tertukarnya sample preparation of work time, Doping and lost when the ore mining.